Investigation of Reactions Between Isothiazolinones and Cysteamine by Reactive Paper Spray Ionization Mass Spectrometry (Reactive PSI MS). (5th December 2019) - Choi, Soobin; Cha, Sangwon
Abstract : Reactive ionization with atmospheric pressure ionization (API) methods have been utilized for mass spectrometry (MS) to enhance ionization efficiency of an analyte, to recognize a specific functional group of an analyte, and to investigate reaction pathways or intermediates for a certain in situ reaction. Paper spray ionization (PSI) is one of the major API techniques for reactive ionization. In reactive PSI, one of the reactants is usually spotted onto a paper tip and the other reactant is delivered through a spraying solution. After in situ reaction, reaction products are transported to the end of the tip and ionized. In this study, we investigated reactions between isothiazolinones (ITs) and cysteamine (CA) by reactive PSI MS. An IT is a heterocyclic compound that has a conjugated ketone moiety and used as a biocide or a preservative. CA is a stable aminothiol that is often used as a bifunctional covalent modifier. Through reactive PSI MS of ITs with CA, we found that a covalent modification of an IT by CA was possible and sensitivities for ITs were improved compared to conventional PSI MS of ITs that did not employ CA. In addition, possible reaction pathways between ITs and CA during reactive PSI were suggested although we could not confirm a specific reaction pathway in the current study. Abstract : Reactive paper spray ionization (PSI) mass spectrometry (MS) of an isothiazolinone with cysteamine.